Transforaminal intrathecal delivery of nusinersen for older children and adults with spinal muscular atrophy and complex spinal anatomy: an analysis of 200 consecutive injections. (29th May 2020) - Weaver, John J; Hallam, Danial K; Chick, Jeffrey Forris Beecham; Vaidya, Sandeep; Shin, David S; Natarajan, Niranjana; Rad, Nassim; Reis, Joseph; Koo, Kevin S H; Shivaram, Giridhar M; Thibodeau, Ashley; Apkon, Susan; et al.
Abstract : Background: Nusinersen is the only approved treatment for all spinal muscular atrophy (SMA) subtypes and is delivered intrathecally. Distorted spinal anatomy and instrumentation preclude standard approaches for intrathecal access, necessitating alternative techniques for delivery. The purpose of this study is to report technical success and adverse events of transforaminal intrathecal delivery of nusinersen. Methods: 28 patients, mean age 24.1±9.8 years (range 10.0–51.0 years), with intermediate or late onset SMA, underwent a combined 200 transforaminal nusinersen injections. All patients had osseous fusion or spinal instrumentation precluding standard posterior access routes. Patients who underwent nusinersen injections using a technique other than transforaminal lumbar puncture (n=113) were excluded. Technical success, adverse events (AEs) and radiation exposure were recorded. Results: 200 (100%) procedures were technically successful; 6 (3%) required a second level of attempt for access. 187 (93.5%) interventions were completed using cone beam computed tomography (CBCT) with two-axis fluoroscopic navigational overlay. 13 (6.5%) procedures were performed with fluoroscopic-guidance only at subsequent sessions. There were 8 (4.0%) mild AEs and 2 (0.5%) severe AEs; one patient received antibiotics for possible traversal of the large bowel but did not develop meningitis, and one patient developed aseptic meningitis. Mean air kerma was 74.5±161.3 mGy (range 5.2–1693.0 mGy). Conclusion: Transforaminal intrathecal delivery of nusinersen is feasible and safe for gaining access in patients with distorted spinal anatomy. The use of CBCT delineates anatomy and optimizes needle trajectory during the initial encounter, and may be used selectively for subsequent procedures.